(untitled) (Revista Electrónica REDINE, 2018)
This essay was developed to make known everything about the video call that is nothing more than a communication system that allows meetings between dispersed groups to be offered the same information, synchronously and in real time. The use given to the video call, the basic elements, the most outstanding features, types of videoconferences, advantages, limitations and some considerations that should be taken into account in the training process will be announced. It will also be announced the educational use of video calls and the need to incorporate Information and Communication Technologies to higher education, specifically the video call, where an analysis of the educational scenarios in which they are developed will be made. educational situations makes sense their employment and how this develops. The compilation of information from this essay is based on the authors Adame (2013), Álvarez (2011), Bravo (2000), Chacón (2003), García and others (2015), Posada (2014) and Sevillano (1998).